Desarrollo de un prototipo detector de drones cuadricópteros en espacios restringidos mediantes firmas acústicas de sus motores - Beltrán Eras, Joel Luis (2018)
The present technical project is to develop a prototype detector of quadrocopters, which is aimed at entities that wish to maintain privacy in their properties, and students in the field of technology, providing new knowledge about DRONES detectors. The development of the detector is based on the implementation of an algorithm in an embedded programming to classify acoustic patterns. The identification process of the motor sound in a quadcopter drone is similar to voice recognition. The objective is to take an acoustic signal of the motors as an input through a microphone to, finally, recognize if the sound perceived comes from the drone. This process consists of three parts: first, the extraction of acoustic characteristics of the drone to store them in the database; secondly, the processing of patterns that starts with the conditioning of the signal, so they can be analyzed in the programming card; finally, the comparison of the signal input with each stored pattern. The detection tests were performed with three drones, and the results of drone detection are the following: 97% of detection with 15 meters of distance, a percentage higher than 70% of detection with 20 meters of distance, and with 25 meters, the percentage is lower than 20% of detection. With these results, it was proven that the detector recognizes the presence of drones at a distance lower than 22 meters. Once verified that the signals belong to this type of unmanned aircraft (drone), an alarm is beamed through a GSM module to a Smartphone.